Education, State, and Psychology: A Study of Students' Pre- and Post-Perceptions of Training Intervention - Khatri, Puja; Raina, Khushboo (Prabandhan: Indian Journal of Management, 2019)
The study undertaken was an endeavor to understand the pre- and post-effects of state intervention on the perceptions of the ultimate stakeholders, that is, students engaged in education at the college level, with regard to their perceptions toward the effort taken by the state in enhancing higher education possibilities, their attitudes toward the state, and the level of trust that these students had in terms of the perception about education system practices and policies that are formulated by the state and ability of the government to bring about education reforms. The study used a quasi-experimental design. A self-constructed questionnaire containing 57 items was administered to 145 students. Cronbach's alpha reliability of the questionnaire was found to be .95. Our study sample comprised of education institutes at the undergraduate level in and around Delhi-NCR. This was followed by an awareness training by faculty about government interventions with regard to the policies introduced for enhancing the quality of education. The same set of students was asked to fill the questionnaire again after the sensitivity intervention to record their post-intervention responses. Personal interview technique was also used to probe certain issues to get further clarity. A paired t-test was used to compare two population means, wherein we had students engaged in an intervention and a pre- and post-analysis was conducted. The paper highlighted a clear requirement of many such government interventions and approaches to implement them at the realistic level on the one hand, and enforcement of psychological understanding and protean career orientation by faculty and institutions on the other hand.